“Epystemologically Different Worlds”: from J. Uexküll to G. Vakariu - Egor V. Falev (RUDN Journal of Philosophy)
The research deals with the concept of “epistemologically different worlds” introduced by Gabriel Vacariu and its background in European science and philosophy, since the beginning of the twentieth century. It is shown that the accusation of plagiarism made by Vacariu against Marcus Gabriel is groundless, firstly, because Gabriel’s concept of “semantic fields” ( Sinnfeld ) is not identical to the concept of epistemologically different worlds, and secondly, because in the twentieth century, similar concepts appeared, starting with the concept of “Umwelt” by Jakob Uexküll (1909). Paying tribute to the revolutionary shift produced by this concept of Uexküll, the author traces the direct and indirect philosophical references and modifications that the concept of umwelt produced in the phenomenology of the late E. Husserl, the fundamental ontology of M. Heidegger and the neurophenomenology of F. Varela. It is shown that both Husserl’s concept of “lifeworld,” Heidegger’s “world-formation,” and Varela’s “structural coupling,” on the one hand, go back to Uexküll’s concept of Umwelt, on the other hand, can be summarized under the general notion of “epistemologically different worlds.” Thus, while refusing to recognize Vacariu’s priority in the creation of this concept, the conclusion is made about the productivity and heuristic value of the term introduced by Vacariu. We also propose a conventional classification of 5 stages of overcoming representativism, in which different variations of the concept of epistemologically different worlds correspond to the last three stages. However, the interpretation of the “phenomenon of the world” developed by M. Heidegger in the second part of his lectures, The Fundamental Concepts of Metaphysics, is considered logically superior. In these lectures, Heidegger draws from J. Uexküll’s concept of the Umwelt and develops an original project of “philosophy of nature,” embedded as a part of his “fundamental ontology.” Here, he not only analyzes the difference between the animal world and the human phenomenon of the world but, on this basis, rethinks the nature of life anew as such and the specificity of the human mode of being and relation to the existent things. Heidegger’s key conclusion for the concept of epistemologically different worlds is that the notion of “existence” applies only within the human world and is inapplicable to the animal umwelt.